HUBUNGAN DUKUNGAN SOSIAL DAN KECEMASAN DALAM MENGHADAPI PERSALINAN PADA IBU HAMIL TRIMESTER KETIGA - Triana Indri Maharani; Muhammad Fakhrurrozi (Universitas Gunadarma, 2014)
The aim of this study is to examine the correlation between social support and anxiety in pregnant women toward giving birth. Participants of this research are 100 pregnant women whom already toward giving birth with 28 until 28 weeks pregnant period. The result shows that the level of social support felt by the participants is in moderate toward high, and the anxiety is moderate toward low. There is also negative correlation between social support and anxiety toward giving birth. It is mean that the higher social support felt by the participants, the lower anxiety they faced. Keywords: Social support, Anxiety toward giving birth, Pregnant women